The Inheritance Dispute Settlement In Court - Armunanto Armunanto (Jurnal Akta, 2021)
The purpose of this study is regarding the settlement of inheritance law disputes, which is one of the reasons a person gets an inheritance, including marriage, blood relations, parents or close sibling relationships or because of testament. This has also been regulated in the provisions of the civil law code of the Civil Code B.W, because someone receives an inheritance because of a nashab/kinship relationship and because of marriage. Meanwhile, for the occurrence of inheritance, it is necessary to have the following elements: 1. The existence of a person who dies (erflater) The person who dies is the person who leaves the inheritance and is called the heir. 2. There are people who are still alive (erfgenaam) people who are still alive, namely people who according to the law or testament are entitled to inherit from the person who died. They are called: Heirs. 3. The existence of objects that are left behind (erftenis, nalatenschap) objects that are left behind are things that are left by the testator at the time of his death, which is called inheritance. The form of this inheritance can be in the form of Activa (receivables, bills) or Liabilities (debts). Problems regarding the distribution of inheritance have basically been regulated in the legal provisions in Indonesia. Both in the provisions of the civil code and in the provisions of the compilation of Islamic law. Where are the provisions regarding Islamic inheritance disputes whose dispute resolution authority is in the religious courts. As for people who are non-Muslims, the settlement process is in the state court. Where in its implementation it must be able to reflect a sense of justice, while still upholding the principle of kinship that applies in the social life of the community.